Recorrência cirúrgica da Doença de Crohn e seus fatores preditores em uma coorte de pacientes acompanhados em ambulatório de referência - Cristiane de Souza Bechara (2013)
Crohn's Disease (CD) is characterized by a chronic and recurrent transmural inflammation with different phenotypes, according to the Montreal classification. Despite the development of clinical treatment, about 75% of CD patients still require surgical treatment and 16 to 65% require another operation in 10 years. This study aimed to evaluate the surgical recurrence and possible predictors in patients operated for CD. It was retrospectively studied a cohort of 125 patients with CD who underwent surgery between January 1992 and January 2012 and were regularly monitored at Inflammatory Bowel Disease Outpatient Clinic of UFMG. The gender distribution was similar, being 50.4% female, with a mean age of 46.12 years, the majority (63.2%) diagnosed between 17 and 40 years. The ileum was involved in 58.4% and behaviors disease was stenosing in 44.8% and penetrating in 45.6% of patients. Perianal disease was observed in 26.4% of cases. The average follow-up time was 152.40 months, and the first operation was performed 29 months on average after initial treatment. Surgical recurrence was observed in 29.6% with a mean of 68 months until the second operation. It was observed that ileocolic location, penetrating behavior and presence of perianal disease were significantly associated with surgical recurrence. The longer time of disease progression was also associated with a greater number of surgeries, whereas age above 40 was most often related to the need for emergency surgery. We conclude that the CD in its most invasive and prolonged forms, especially with ileocolic location and perianal involvement tends to recur more frequently after surgery, and emergency interventions were more common in patients over 40 years.